Displacing the state: religion and conflict in neoliberal Africa - Smith, James Howard; Hackett, Rosalind I. J.; Appleby, R. Scott (Kroc Institute series on religion, conflict, and peace building, 2012)
Intro -- Contents -- Foreword -- Acknowledgments -- Introduction -- Part 1 -- 1 Forgiveness with Consequences -- 2 Making Peace with the Devil -- New Religious Movements, Enduring Social Tensions -- 3 The Mungiki Movement -- 4 Magic as Identity Maker -- 5 Religion, Politics, and Gender in Zimbabwe -- Part 3 -- 6 "Devil Bustin' Satellites" -- 7 Mediating Armageddon -- 8 "The Domestic Relations Bill" and Inter-Religious Conflict in Uganda -- Contributors -- Index.